2017
DOI: 10.4992/jjpsy.88.16327
|View full text |Cite
|
Sign up to set email alerts
|

Phonological familiarity facilitates lexical decision but not semantic categorization

Abstract: Rika Mizuno and Takao Matsui (Chubu University)Homophone effects, which refer to the phenomenon in which lexical decision times are longer for homophones than nonhomophones, have not been consistently observed for Japanese homophones with multiple mates. Mizuno and Matsui (2016) explored this inconsistency, finding that phonological familiarity of homophones-namely, the total frequencies of a homophone and all of its mates-can countervail homophone effects. However, it remains unclear why phonological familiar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Essentially, by increasing the overall phonological familiarity of the targets, phonologically similar targets may function as higher frequency words. Higher phonological familiarity has been shown to facilitate lexical decision latencies in English (e.g., Yates, 2005; Yates et al, 2004) and in logographic Kanji and Chinese words (e.g., Mizuno & Matsui, 2017; Ziegler et al, 2000). Specifically, Ziegler et al (2000) reported that more phonologically similar Chinese words (words with homophones) are responded to significantly faster both in a naming task and lexical decision task (also see Tse & Yap, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Essentially, by increasing the overall phonological familiarity of the targets, phonologically similar targets may function as higher frequency words. Higher phonological familiarity has been shown to facilitate lexical decision latencies in English (e.g., Yates, 2005; Yates et al, 2004) and in logographic Kanji and Chinese words (e.g., Mizuno & Matsui, 2017; Ziegler et al, 2000). Specifically, Ziegler et al (2000) reported that more phonologically similar Chinese words (words with homophones) are responded to significantly faster both in a naming task and lexical decision task (also see Tse & Yap, 2018).…”
Section: Discussionmentioning
confidence: 99%